2021
DOI: 10.1007/s10111-021-00683-y
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging human factors in cybersecurity: an integrated methodological approach

Abstract: Computer and Information Security (CIS) is usually approached adopting a technology-centric viewpoint, where the human components of sociotechnical systems are generally considered as their weakest part, with little consideration for the end users’ cognitive characteristics, needs and motivations. This paper presents a holistic/Human Factors (HF) approach, where the individual, organisational and technological factors are investigated in pilot healthcare organisations to show how HF vulnerabilities may impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 110 publications
(133 reference statements)
2
67
0
1
Order By: Relevance
“…Individual or personal factors investigate the individual reasoning and decision-making behind security behavior [ 95 ]. This study identified 31 distinct individual factors ( Table 8 ) from the selected studies that empirically influence information security behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Individual or personal factors investigate the individual reasoning and decision-making behind security behavior [ 95 ]. This study identified 31 distinct individual factors ( Table 8 ) from the selected studies that empirically influence information security behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Protection and defense of analogue and digital electronic devices, their communications channels, their processing and control logic and algorithms stands better to improve in Cameroon when organizations begin to proactively adopt a user-centered perspective. According to Pollini et al (2021), better cyber-security culture does not always correspond with more rule compliant behavior; conflicts among cybersecurity rules and procedures may even trigger human vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
“…2021). Cybersecurity threat is becoming more frequent and the threat according to Pollini, Callari, and Tedeschi (2021) include: online fraud, distributed denial of service, drive by download, and social engineering attacks. The changing nature of cybersecurity is exploiting instances of human error or negligence along with system vulnerabilities.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need of such kind of research so that railway workforce will be aware of cyber hygiene to be followed. This can be done by transferring cybersecurity workforce knowledge to railways from other available literature such as, NIST guide to the National Initiative for Cybersecurity Education (NICE) cybersecurity workforce framework, 140,141 cybersecurity workforce development and training for critical infrastructure and nation, [142][143][144] human-centric cybersecurity research, 145 human factors in cybersecurity [146][147][148] and soon. Some of the researchers have provided a set of recommendations and literature to enhance cybersecurity workforce culture within railway organizations.…”
Section: Not Enough Studies On Human Factormentioning
confidence: 99%